Ketamine with Midazolam and Ketamine alone as oral premedication in children: a randomized trial - Thakur, Jaya Prakash; Rana, Resham Bahadur; Pokharel, Abhay (Journal of Society of Anesthesiologists of Nepal, 2018)
Background: Fear of operation, injections, physicians and peculiar operation theatre environment where children are separated from their parents prior to anesthesia invariably produce traumatic experiences in tender mind of young children. Midazolam and Ketamine are useful for oral premedication in children to allay anxiety, allow separation from parents and to ensure smooth induction. Methodology: It was a prospective, randomized, double-blinded and comparative study conducted in 80 children of ASA I and II aged 1-6years undergoing elective ophthalmological procedures under general anesthesia. Children were randomized and divided into two groups, K received 4mg/kg of Ketamine and MK received 0.2mg/kg of Midazolam+2mg/kg of Ketamine peroral. Sedation level, ease of parental separation and ease of mask acceptance were evaluated within 20-30 minutes on a 4-point scale. The time to achieve modified Aldrete score of ≥9 was also noted. Results: Two groups were identical regarding age, sex, weight and ASA status. In sedation score, 31(77.5%) children in group K and 35(87.5%) children in group MK were awake, calm and quite (score3)(p=0.50). In parental separation score, 34(85%) children in group MK and 25(62.5%) children in group K have good separation, awake and calm (score2) (p=0.04). In mask acceptance score, 34(85%) children in group MK and 17(42.5%) children in group K were calm, awake, cooperative, accepting Mask (score1)(p=0.001). Time of recovery in group K was 17.92}6.50min whereas in group MK was 17.80}4.059min(p=0.91). Conclusion: Ketamine 4mg/kg and combination of Midazolam 0.2mg/kg with Ketamine 2mg/kg are equally effective but low dose combination is safe and superior. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 66-73